Virtualization Security Combining Mandatory Access Control and Virtual Machine Introspection - Thu Yein Win; Tianfield, Huaglory; Mair, Quentin (Proceedings of the 2014 IEEE/ACM 7th International Conference on Utility and Cloud Computing, 2014)
Virtualization has become a target for attacks in cloud computing environments. Existing approaches to protecting the virtualization environment against the attacks are limited in protection scope and are with high overheads. This paper proposes a novel virtualization security solution which aims to provide comprehensive protection of the virtualization environment.